Pedagogical conditions of formation of creativity at future teachers - Ayaulym Septemirova, Abdimanap Zholdasbekov,; Мyrzabekov, Erzhan; Karlygash Zholdasbekova, Yenilkhan Kozybaev,; Mussabekova, Gulnar (Opción, 2019)
The research aims to reveal the level of formation of creativity at future teachers, to determine the pedagogical conditions and to provide their realization via theoretical, diagnostic, empirical, experimental and mathematical statistics and graphic representation of results methods. As a result, the level of formation of creativity at future teachers is revealed; pedagogical conditions were determined and the author’s methodology of formation of creativity at future teachers is presented. In conclusion, the process of formation of creativity at future teachers will be effective, if formation of creativity of future teachers is carried out on the basis of the developed model.